UniKL Business School: Matters Beyond Ranking Towards Becoming A World Class University - Arman Hj Ahmad; Professor Dr Wan Sabri Wan Hussin (Cita konsultindo, 2023)
Past researches revealed that, to be a world class institution, the institution itself need to make sure that everything inside are highly strong, excellent and then it can be ready to be claimed as a world class. In the other word, from A to Z of the university should and compulsorily achieved the world class standard before it can be claimed as the world class institution. This paper focuses on some issues need to be highlighted by Universiti Kuala Lumpur Business School by its management in order to facilitate the university to climb the ladder to be the world class ranking higher institution among others in the region. The issues such as manpower quality, students’ quality, graduate quality, teaching quality, learning quality, facilities quality and the overall operational quality are crucial issues need to be focused by the top management in realizing and achieving the dream of the institution to be the world class university. Careful analyses of eighteen articles with different themes on world class university and management of higher learning institution yields some insights on issues prevalent in the matter. Finally, this paper proposes an integrated model for world class university management which highlights the important management issues that need serious attention from the management. The model is constructed based on insights drawn from the analyses of the articles. The model may be used as a guide for UniKL Business School and may be useful tools for consultants to use in handling tasks relating to the developing world class university.